Análise do ciclo de vida da carne bovina: um estudo de caso na área de proteção ambiental do Ibirapuitã - Vargas, Letícia Paludo (2013)
This paper analyzes the socioeconomic and environmental impacts caused by the extensive production systems of beef cattle. In this sense, a case study was conducted in Estância do 28, owned by Fundação Maronna, located in Área de Proteção Ambiental do Ibirapuitã, at the southern state of Rio Grande do Sul. Within the methodological resources, the main methodology was the Life Cycle Assessment of beef cattle supply chain, which allows to determine the total environmental impact from the production and consumption of "beef product". Moreover, the IPCC software was used as an auxiliary tool, in order to analyze and quantify carbon emissions from beef cattle. The data analysis collected in the Estância do 28, delimited to the years 2010, 2011 and 2012, in order to assess the environmental impacts of meat production on the property. The research demonstrates that the emissions are derived from enteric fermentation of beef cattle, such as land use changes and animal waste. The account of carbon costs, marketing and consumption of beef shows that both emissions and total costs are low when compared to animal production within the property. With regard to carbon emissions resulted of transport, it was found that differences in the level of emissions are negligible, regardless of the types of market and its distances. Thus, it can be seen that animal production is the chain link that emits the most carbon. Therefore, its measure should be centralized at this stage of the chain, in order to reduce environmental impacts.